Halal tourism is traveling fast: Community perceptions and implications. (December 2020) - Moshin, Asad; Brochado, Ana; Rodrigues, Helena
Abstract: Although halal tourists are a growing, attractive market segment, research on the topic is still incipient. This study sought to answer three questions. What opportunities and challenges exist for those promoting halal tourism? What are tourism stakeholders and communities' perceptions of halal tourism? How can halal tourist facilities enhance their image in order to become favorite halal tourism destinations? The research was conducted in New Zealand and based on a one-day symposium comprising panel discussions of the questions. The 100 participants were tourism and hospitality professionals, government authorities, community leaders, ethnic community representatives, business owners, and Muslim leaders. The findings have theoretical, managerial, and societal implications due to halal tourists' distinctive needs, including their religious and social travel motivations. Highlights: Identifies the opportunities and challenges of those promoting halal tourism. Examines tourism stakeholders and communities' perceptions of halal tourism. Explains how facilities' image help them become a favorite with halal tourists. Details an innovative research design: 1-day symposium with 100 stakeholders.